2013
DOI: 10.7860/jcdr/2013/4750.2948
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Pranayama/Alternate Nostril Breathing on the Parasympathetic Nervous System in Young Adults

Abstract: Background and Aim: Pranayama, the art of breath control, is considered to be the heart of yogic exercises. The present study was performed with the aim of evaluating the effect of Pranayama/ Alternate Nostril Breathing (A.N.B.) on the parasympathetic nervous system in healthy young adult males. Methods:A comparative account of the expiratioin: inspiration ratio (E:I ratio) and the orthostatic tolerance test (30:15 ratio) at the basal level, at the start of the study and after the practice of A.N.B for 5 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 3 publications
2
31
0
2
Order By: Relevance
“…7,22 Five studies evaluated effects of 6-12 weeks of ANB on the autonomic nervous system (except study by Jain et al, which consisted of a single session) by recording heart rate response to the following tests: deep breathing, orthostatic tolerance, HR in response to immediate standing, standing to lying ratio, 30:15 ratios, valsalva ratio, tachycardia ratio, bradycardia ratio, expiration to inspiration ratio, as well as blood pressure response to hand grip and cold pressure tests. 26,27,34,37,44 These studies noticed enhanced autonomic functioning in response to the following tests: deep breathing, orthostatic tolerance, HR in response to immediate standing, standing to lying ratio, 30:15 ratio, Valsalva ratio except for Pal et al, (who reported no significant changes in Valsalva ratio but improved results for other autonomic function tests). Although Mourya et al, reported increased BP in response to the isometric hand grip and cold pressure tests, Dhavijay et al, noticed decreased diastolic blood pressure in response to hand grip test.…”
Section: Anb and Autonomic Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…7,22 Five studies evaluated effects of 6-12 weeks of ANB on the autonomic nervous system (except study by Jain et al, which consisted of a single session) by recording heart rate response to the following tests: deep breathing, orthostatic tolerance, HR in response to immediate standing, standing to lying ratio, 30:15 ratios, valsalva ratio, tachycardia ratio, bradycardia ratio, expiration to inspiration ratio, as well as blood pressure response to hand grip and cold pressure tests. 26,27,34,37,44 These studies noticed enhanced autonomic functioning in response to the following tests: deep breathing, orthostatic tolerance, HR in response to immediate standing, standing to lying ratio, 30:15 ratio, Valsalva ratio except for Pal et al, (who reported no significant changes in Valsalva ratio but improved results for other autonomic function tests). Although Mourya et al, reported increased BP in response to the isometric hand grip and cold pressure tests, Dhavijay et al, noticed decreased diastolic blood pressure in response to hand grip test.…”
Section: Anb and Autonomic Nervous Systemmentioning
confidence: 99%
“…[7][8][9][10][11][12][13]27,29,31,[37][38][39][40][41] Six studies included the following pattern: breathe out through left nostril, then breathe in through right nostril and repeat this pattern once, twice or three times, before switching the nostrils to breathe out through right nostril, breathe in through left nostril and repeat this once, twice or three times before switching again. 28,[42][43][44]46 Another study involved a mixed pattern of cycles of unilateral nostril breathing, cycles of normal breathing, cycles of opposite unilateral nostril breathing and cycles of alternate nostril breathing. 3 Seven studies instructed subjects to focus on their breath while practicing ANB.…”
Section: Alternate Nostril Breathing Techniquementioning
confidence: 99%
“…In a pilot study in which a 12-week yoga intervention among old age adults was performed to test if fear of falling would decrease as well as body balance would improve, static balance raised by 4% (p = 0.045). The yoga practice included breathing exercises (pranayama) [6,21]. In another experiment, carried out by Santanella et al [22], yoga practitioners were randomized into 4 month-long training programmes for 2 groups: respiratory exercises (yoga group, experimental, n = 15) and the stretching group (control, n = 14).…”
Section: Discussionmentioning
confidence: 99%
“…Yoga based slow breathing exercise might increase vagal tone which shift sympathovagal balance towards parasympathetic predominance 9,[12][13][14][17][18]27 .Moreover SBE might also increases baroreflex sensitivity 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers reported about improvement of cardiac autonomic nerve function when the healthy subjects performed yoga based slow breathing exercise [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%